Engaging with the Unreliable Narrator : Teaching Literary Perspective and Subjectivity - Hind HANAFI (Akofena)
Abstract : This paper examines the pedagogical value of teaching unreliable narrators in literature to enhance students’ understanding of narrative perspective, bias, and subjectivity. The unreliable narrator—characterized by a departure from traditional narrative authority—serves as a compelling medium for students to confront interpretive ambiguity and narrative skepticism. Drawing from both narrative theory and cognitive narratology, this study explores how unreliable narration can be systematically introduced and analyzed in the literature classroom, prompting critical examination of the text and reflection on readers’ own biases. We discuss various types of unreliable narrators, including naïve, morally ambiguous, and disoriented narrators, to demonstrate how each type uniquely challenges students to reassess narrative reliability and deepen their analytical skills. Classroom strategies, such as close reading exercises and open-ended discussion formats, are presented as methods to help students identify signals of unreliability, recognize the role of ambiguity, and develop flexible interpretative skills. Additionally, we consider the challenges associated with teaching unreliable narration, such as student resistance to narrative ambiguity, and the need for culturally sensitive approaches in texts with ethically complex narrators. This study highlights how engaging with unreliable narrators fosters transferable critical thinking skills, equipping students to analyze not only literature but also diverse media and real-world narratives with a betterunderstanding of bias and perspective. Implications for broader pedagogical practices in literature and interdisciplinary education are discussed. Keywords: Unreliable narrator, narrative perspective, cognitive narratology, teaching strategies, critical thinking.